Internal herniation of small bowel through the minimizer ring after banded one anastomosis gastric bypass: Case report with diagnosis and management of a rare complication. Issue 4 (July 2022) - Sensi, Bruno; Beomonte Zobel, Lorenza; Forte, Valerio; Alicata, Federica; Procaccini, Chiara; Pavoncello, David; Arcudi, Claudio; Bianciardi, Emanuela; Gentileschi, Paolo
Abstract: Introduction: One Anastomosis Gastric Bypass has been increasingly performed in the setting of bariatric surgery. The addition of gastric pouch banding (BOAGB) may reduce weight regain in the long term. BOAGB may rarely be complicated by MiniMizer ring-related affections. This article reports for the first time a case of bowel obstruction due to internal hernia (IH) through the ring itself, occurring 15 months after BOAGB. Case report: A 55 years-old woman presented with unspecific symptoms of sub-acute bowel obstruction 15 months after BOAGB. Work-up revealed IH through the MiniMizer ring and its erosion into the liver. Successful management included laparoscopic ring removal and adhesion-lysis. Postoperative course was uneventful. Discussion and conclusion: IH through MiniMizer ring is a rare complication of BOAGB and awareness of this possibility may help diagnosis and prevention. Diagnosis requires high index of suspicion and per-oral contrast CT. Successful management entails laparoscopic device removal. Prevention includes non re-absorbable suture fixation and adequate gastric pouch encirclement.